(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Small groups of researchers researching Indian fish have used truss morph metrics todiscriminate between various species. Overfishing is caused by the use of ever-more-advanced fishinggear. Researchers examined the length-weight correlations (LWRs) of 588 fish from eight families,thirteen genera, and fourteen. The Yamuna River Firozabad (a Yamuna River tributary) was investigated.All species had a mean b value of 2.96 and a p-value of 0.001 for b = 2.96. In light of the Yamuna River’sfirst-ever connection to the Ken River, conservation and management specialists believe these resultsare critical since length-weight data has never been obtained. In order to effectively manage fisheries, weset out to determine the LWRs of two previously unstudied rivers.